Impacts of willow and miscanthus bioenergy buffers on biogeochemical N removal processes along the soil–groundwater continuum. Issue 1 (29th February 2016) - Ferrarini, Andrea; Fornasier, Flavio; Serra, Paolo; Ferrari, Federico; Trevisan, Marco; Amaducci, Stefano
Abstract: In this article, the belowground and aboveground biomass production in bioenergy buffers and biogeochemical N removal processes along the soil–groundwater continuum was assessed. In a sandy loam soil with shallow groundwater, bioenergy buffers of miscanthus and willow (5 and 10 m wide) were planted along a ditch of an agricultural field (AF) located in the Po valley (Italy). Mineral N forms and dissolved organic C (DOC) were monitored monthly over an 18‐month period in groundwater before and after the bioenergy buffers. Soil samples were measured for inorganic N, DOC, microbial biomass C (MBC) and N (MBN), and potential nitrate reductase activity (NRA). The results indicated that bioenergy buffers are able to efficiently remove from groundwater the incoming NO3 ‐N (62% – 5 m and 80% – 10 m). NO3 ‐N removal rate was higher when nitrate input from AF increased due to N fertilization. Willow performed better than miscanthus in terms of biomass production (17 Mg DM ha −1 yr −1 ), fine root biomass (5.3 Mg ha −1 ) and N removal via harvesting (73 kg N ha −1 ). The negative nonlinear relationship found between NO3 ‐N and DOC along the soil–groundwater continuum from AF to bioenergy buffers indicates that DOC:NO3 ‐N ratio is an important controlling factor for promoting denitrification in bioenergy buffers. Bioenergy buffers promoted soil microbial functioning as they stimulated plant–microbial linkages by increasing the easily available C sources for microorganisms (as DOC). First, willow and miscanthus promoted high rates of biological removal of nitrate (NRA) along the soil profile. Second, rhizosphere processes activated the soil microbial community leading to significant increases in MBC and microbial N immobilization. Herbaceous and woody bioenergy crops have been confirmed as providing good environmental performances when cultivated as bioenergy buffers by mitigating the disservices of agricultural activities such as groundwater N pollution.